Synthesis, structure and rearrangement of iodinated imidazo[1,2-c]pyrimidine-5(6H)-ones derived from cytosine - Jansa, Josef; Lyčka, Antonín; Růžička, Aleš; Grepl, Martin; Vaněček, Jan (Tetrahedron, 2015)
We describe mild and selective iodination of various 8-substituted imidazo[1,2-c]pyrimidine-5(6H)-ones (ethenocytosines). Starting ethenocytosines were obtained by cyclization of 5-halogenocytosines with chloroacetaldehyde or by subsequent Suzuki–Miyaura cross-coupling between 8-iodoimidazo[1,2-c]pyrimidine-5(6H)-one 1d and corresponding arylboronic acids. When imidazo[1,2-c]pyrimidine-5(6H)-one or 8-iodoimidazo[1,2-c]pyrimidine-5(6H)-one 1d was iodinated by N-iodosuccinimide (NIS) in DMF, pure 3,8-diiododerivative 2d was obtained. Under basic or acidic conditions, this molecule is subject to rearrangement into 2,8-diododerivative 3d, which can be subsequently iodinated to 2,3,8-triododerivative 4d. Since the positions of iodine atoms on the imidazole ring could not be determined convincingly from NMR spectra only, X-ray analysis of 2d was carried out with the aim of confirming the structure undoubtedly. The same sequence of reactions was applied to another eight ethenocytosines, providing excellent regioselectivity, easy rearrangement and high yields of iodinated products. All ethenocytosines were properly characterized by 1H, 13C and 15N NMR spectroscopy. [Display omitted]